A lithium ion battery, a preparation method thereof and an electric device
Patent Information
- Application Number
- CN202611297815.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]现有技术通常分别限定高镍正极颗粒粒径、单晶与多晶比例、隔膜陶瓷层材料、陶瓷层厚度或隔膜透气度,难以表征陶瓷层与正极在装配状态下形成的真实接触关系,也难以区分界面近表层损伤与辊压引起的体相基础损伤
[0016]本发明具有以下有益效果:本发明提供一种勃姆石-高镍正极配对界面受控的锂离子电池,通过限定真实接触长度比例、非接触区间隙参数和界面近表层相对体相的分类损伤差,使界面液相传输与机械载荷处于匹配状态,从而降低正极电荷转移阻抗及其增长率,并改善高温存储、倍率放电和循环性能。
Smart Images

Figure CN122992145A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a lithium-ion battery, its preparation method, and an electrical device thereof. Background Technology
[0002] High-nickel layered lithium-containing transition metal oxides possess high discharge specific capacity and operating voltage, making them crucial cathode materials for high-energy-density cylindrical lithium-ion batteries. To balance compaction density, rate performance, and mechanical stability, the cathode active material layer can simultaneously contain large-diameter polycrystalline secondary particles and small-diameter single-crystal particles. Large-diameter polycrystalline secondary particles, formed by the aggregation of multiple primary particles, can provide high compaction density, but their primary particle boundaries are prone to cracking under rolling, winding constraints, and cyclic lattice changes. Small-diameter single-crystal particles can fill some of the interparticle gaps and improve local contact, but they cannot completely eliminate stress concentration on the cathode surface.
[0003] In cylindrical battery cells, to improve the heat resistance and puncture resistance of the separator, an inorganic porous coating is typically applied to the surface of the porous base film. When the porous coating formed by boehmite particles is placed opposite the high-nickel cathode, the surface undulations of the coating, the separator winding tension, and the core shaping constraints collectively determine the contact, gap, and embedding state between the boehmite porous coating and the cathode active material layer. Insufficient contact can lead to excessively long local electrolyte channels, uneven ion flow distribution, and inconsistent reactions on the cathode surface; excessive contact or excessive embedding can concentrate the radial load on the surface of the polycrystalline secondary particles, causing the primary particle boundaries to open, the particles to locally pulverize, and new side reaction interfaces to form.
[0004] Existing technologies typically define the particle size of high-nickel cathode particles, the ratio of single-crystal to polycrystalline materials, the material of the separator ceramic layer, the thickness of the ceramic layer, or the permeability of the separator separately. This makes it difficult to characterize the true contact relationship between the ceramic layer and the cathode in the assembled state, and also difficult to distinguish between near-surface interfacial damage and bulk damage caused by rolling. Using only the full-layer crack ratio can easily mask localized interfacial stress; using only the separator thickness or particle size cannot indicate whether the load has been transferred to the high-nickel particles. Therefore, it is necessary to establish a quantitative relationship between interfacial contact state, localized damage response of different particle types, and cathode electrochemical kinetics to improve high-temperature storage, rate discharge, and cycle performance.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a lithium-ion battery, its preparation method, and an electrical device thereof, which aims to improve high-temperature storage, high-rate discharge, and cycle performance.
[0007] This invention is implemented as follows: In a first aspect, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The positive active material layer comprises large-diameter polycrystalline secondary particles and small-diameter single-crystal particles. Both the large-diameter polycrystalline secondary particles and the small-diameter single-crystal particles are layered lithium-containing transition metal oxide particles. In the layered lithium-containing transition metal oxide particles, the molar percentage of nickel in the total transition metal is greater than or equal to 88%. The membrane includes a porous base membrane and a boehmite porous coating disposed on at least one surface of the porous base membrane, the boehmite porous coating facing the positive electrode active material layer; On the cross section maintaining the assembly relationship between the boehmite porous coating and the positive electrode active material layer, the section with a local spacing of no more than 0.20 μm and a continuous length of no less than 0.50 μm along the interface direction is identified as the actual contact section. The ratio of the sum of the projected lengths L1 of all actual contact sections to the total projected length L2 of the statistical interface is taken as the actual contact length ratio C1, where C1 = L1 / L2 × 100%, and the range of C1 is 20% to 70%. Taking the surface of the boehmite porous coating above the positive electrode active material layer as z=0, the region 0≤z≤10μm is defined as the near-surface layer Z1, and the region 15μm≤z≤25μm is defined as the bulk region Z2. F1, F2, F3, and F4 represent the proportions of damaged large-diameter polycrystalline secondary particles in Z1, Z2, Z1, and Z2, respectively, and are further defined as ΔF=∣(F1 F2) (F3 F4) | Calculate the difference in classification damage, where ΔF is the difference between the percentages, ranging from 2% to 15%.
[0008] In optional embodiments, the equivalent circular diameter of the large-diameter polycrystalline secondary particles is 8 μm to 20 μm, and the equivalent circular diameter of the small-diameter single-crystal particles is 1 μm to 6 μm; preferably, the equivalent circular diameter of the large-diameter polycrystalline secondary particles is 10 μm to 16 μm, and the equivalent circular diameter of the small-diameter single-crystal particles is 1.5 μm to 5.0 μm; the mass ratio of the large-diameter polycrystalline secondary particles to the small-diameter single-crystal particles is 60:40 to 85:15. In optional embodiments, C1 ranges from 30% to 60%. Preferably, the local spacing is measured point by point in the non-real contact section, and the 90th percentile is used as the gap parameter D1, with D1 ranging from 0.30 to 2.00 μm; the baseline fitted to the surface of the positive electrode active material layer without obvious depressions is used as a reference, and the 90th percentile of the maximum normal depth of boehmite particles entering below the fitted baseline is used as the embedding parameter D2, with D2 ranging from 0.20 μm to 1.50 μm.
[0009] In an optional implementation, F1 ranges from 8% to 25%, F2 ranges from 3% to 12%, F3 ranges from 1% to 8%, F4 ranges from 0.5% to 5%, and ΔF is from 3% to 10%.
[0010] In an optional implementation, G1=(R1) The high-temperature positive electrode charge transfer resistance growth rate G1 is calculated as R2) / R2×100%, where G1 is not greater than 35%, R1 represents the positive electrode charge transfer resistance after storage at 60℃, and R2 represents the positive electrode charge transfer resistance in the initial state. Preferably, R2 is 15 Ω·cm 2 ~60Ω·cm 2 ; Preferably, according to G2=(R3) The positive charge transfer resistance growth rate G2 over 300 cycles is calculated as R2) / R2×100%, and G2 is not greater than 45%.
[0011] In an optional embodiment, the winding tension of the diaphragm is 0.28N to 0.65N; Preferably, the radial crushing strength of the large-diameter polycrystalline secondary particles is 95 MPa to 145 MPa; Preferably, the thickness of the boehmite porous coating is 1.0 μm to 4.0 μm, and the volume median particle size (D50) of the boehmite particles is 0.10 μm to 3.00 μm.
[0012] In an optional embodiment, the thickness of the positive electrode active material layer on one side is 30 μm to 42 μm, and the difference in thickness of the positive electrode active material layer on the two surfaces of the positive electrode current collector is no greater than 4 μm. Preferably, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector, wherein the negative active material layer comprises artificial graphite and silicon-oxygen-graphite composite material; preferably, the mass ratio of artificial graphite to silicon-oxygen-graphite composite material is 90:10 to 96:4. Preferably, the electrolyte comprises lithium hexafluorophosphate, a carbonate solvent, and a film-forming additive; preferably, the concentration of lithium hexafluorophosphate in the electrolyte is 0.8 mol / L to 1.2 mol / L; the carbonate solvent comprises ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate, with a volume ratio of 20–30:40–50:25–35; the film-forming additive comprises vinylene carbonate, fluoroethylene carbonate, and lithium difluorophosphate, with mass fractions of 1.0%–3.0%, 0.5%–2.0%, and 0.2%–1.0%, respectively. Preferably, the lithium-ion battery is a cylindrical lithium-ion battery with a diameter of 20mm to 22mm, a height of 69mm to 72mm, and a rated capacity of 4.8Ah to 5.2Ah; at least one longitudinal edge of the positive electrode and the negative electrode are respectively provided with tab units formed at intervals along the winding direction, which form an end current collection structure after winding.
[0013] In an optional implementation, at 25±2℃, the 40A platform voltage difference ΔV 40 The maximum surface temperature of the casing during a 40A discharge and within 300 seconds after the discharge is not higher than 75°C. The capacity recovery rate after 7 days of storage at 60°C is not less than 90%, and the capacity retention rate after 600 cycles is not less than 76%.
[0014] In a second aspect, the present invention provides a method for preparing a lithium-ion battery according to any of the foregoing embodiments, comprising: preparing a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte respectively, and then performing winding, heat setting, casing, current collector connection, electrolyte injection, sealing, formation and capacity testing. C1 is adjusted by the diaphragm winding tension, and ΔF is adjusted by the radial crushing strength of the large-diameter polycrystalline secondary particles. Preferably, it further includes adjusting D1 and D2 by adjusting the diaphragm winding tension.
[0015] Thirdly, the present invention provides an electrical device comprising any of the lithium-ion batteries described in the foregoing embodiments or a lithium-ion battery prepared by the preparation method described in the foregoing embodiments.
[0016] The present invention has the following beneficial effects: The present invention provides a lithium-ion battery with controlled boehmite-high nickel cathode pairing interface. By limiting the ratio of the actual contact length, the gap parameter of the non-contact area and the classification damage difference of the near-surface layer of the interface relative to the bulk phase, the liquid phase transport at the interface is matched with the mechanical load, thereby reducing the cathode charge transfer impedance and its growth rate, and improving high-temperature storage, rate discharge and cycle performance. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a schematic diagram of the interface cross-sectional structure between the boehmite porous coating and the high-nickel positive electrode active material layer in the lithium-ion battery of the present invention.
[0019] Icons: 1-Positive current collector; 2-Positive electrode material particles; 3-Boehmite; 4-Non-contact area; 5-Separator substrate. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0021] This invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The following describes each component: [Positive electrode plate] The positive electrode includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The positive active material layer contains large-diameter polycrystalline secondary particles and small-diameter single-crystal particles. Both the large-diameter polycrystalline secondary particles and the small-diameter single-crystal particles are layered lithium-containing transition metal oxide particles.
[0022] The molar content of nickel, relative to the total molar number of transition metal elements excluding lithium and oxygen, shall not be less than 88%, and may be 88%, 90%, 92%, 94%, 96%, 98%, 100%, or any value between these adjacent values. In other words, both large-diameter polycrystalline secondary particles and small-diameter single-crystal particles are high-nickel cathode materials. High-nickel cathodes may employ layered lithium-containing transition metal oxides containing Ni, Co, Mn, and further containing one or more elements from Al, Mg, Zr, Ti, W, B, or Nb; the two types of particles may have the same or different nickel contents.
[0023] The equivalent circular diameter of the large-diameter polycrystalline secondary particles is 8μm to 20μm, such as 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, etc., or any value between these adjacent values, preferably 10μm to 16μm. The equivalent circular diameter of the small-diameter single-crystal particles is 1μm to 6μm, such as 1.0μm, 2.0μm, 3.0μm, 4.0μm, 5.0μm, 6.0μm, etc., or any value between these adjacent values, preferably 1.5μm to 5.0μm. The mass ratio of the large-diameter polycrystalline secondary particles to the small-diameter single-crystal particles is 60:40 to 85:15, such as 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, etc.
[0024] Specifically, the nickel content in the cathode active material was determined using ICP-OES; the equivalent circle diameter of the particles was determined using BSE imaging, and EBSD grain orientation maps were used to distinguish between large-diameter polycrystalline secondary particles and small-diameter single-crystal particles. The nickel content and particle size affect the compaction density, local stress distribution, and cycle stability. Large-diameter polycrystalline secondary particles and small-diameter single-crystal particles can be used in nickel-cobalt-manganese ternary cathode materials.
[0025] Specifically, large-diameter polycrystalline secondary particles refer to positive electrode active material particles formed by the aggregation of no fewer than 10 primary particles, with observable primary particle boundaries or grain orientation differences in the cross-section, and an equivalent circular diameter of 8 μm to 20 μm; small-diameter single-crystal particles refer to positive electrode active material particles whose cross-section does not show multiple primary particle aggregates, have an equivalent circular diameter of 1 to 6 μm, and whose main body is a single crystal orientation region. The formula for calculating the equivalent circular diameter D0 of the particle is as follows:
[0026] Where A0 is the area of the closed contour of the particle.
[0027] Furthermore, the radial crushing strength of large-diameter polycrystalline secondary particles ranges from 95 MPa to 145 MPa, and can be any value between these adjacent ranges, such as 95 MPa, 105 MPa, 115 MPa, 125 MPa, 135 MPa, or 145 MPa. The radial crushing strength of large-diameter polycrystalline secondary particles is calculated using micro-compression load and equivalent diameter, and it affects the classification damage difference and particle integrity.
[0028] Specifically, the radial crushing strength of large-diameter polycrystalline secondary particles was determined using a micro-compression test. Dry powder was spread evenly on a hard plate. Particles with an equivalent circular diameter of 10–16 μm and intact contours were selected. A flat-head pressure device with a diameter of 50 μm was applied at a rate of 0.10 mN / s until a sudden load drop occurred. The crushing load P and the equivalent circular diameter D0 of the particle before loading were recorded. When the unit of P is mN and the unit of D0 is μm, the crushing strength was determined using the formula σ1 = 2800P / (πD0). 2 Calculate the radial crushing strength, and the result is in MPa. Measure 50 particles per batch, and use the median as the radial crushing strength of that batch.
[0029] The thickness of the positive electrode active material layer on one side is 30μm to 42μm, such as 30μm, 32μm, 35μm, 38μm, 40μm, 42μm, etc., or any value between these adjacent values. The thickness difference of the positive electrode active material layer on the two surfaces of the positive electrode current collector is no greater than 4μm, such as 0μm, 1μm, 2μm, 3μm, 4μm, etc., or any value between these adjacent values.
[0030] In some embodiments, the positive electrode active material layer comprises, by mass percentage: 96.5%–98.0% positive electrode active material, 0.5%–1.5% conductive agent, and 1.0%–2.0% binder. The conductive agent may be conductive carbon black, carbon nanotubes, graphene, or a combination thereof. The binder may be selected from polyvinylidene fluoride or a high-potential polymer with equivalent bonding properties, depending on the positive electrode slurry system.
[0031] [Negative electrode plate] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The negative active material layer contains artificial graphite and silicon-oxygen-graphite composite material, with artificial graphite and silicon-oxygen-graphite composite material as the negative active material. The silicon oxide in the silicon-oxygen-graphite composite material has the chemical formula SiOx, where 0.8≤x≤1.3.
[0032] In some embodiments, the negative electrode active material layer comprises, by mass percentage: 90%–96% artificial graphite, 4%–10% silicon-oxygen-graphite composite material, 0.3%–1.0% conductive agent, and 1.0%–2.0% binder. The conductive agent may be conductive carbon black, carbon nanotubes, or a combination thereof; the binder may be a combination of sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0033] [Septum] The separator includes a porous base membrane and a boehmite porous coating disposed on at least one surface of the porous base membrane, the boehmite porous coating being assembled facing the positive electrode active material layer.
[0034] Specifically, the boehmite porous coating is a ceramic coating layer that does not alter the polyolefin-based membrane itself. It utilizes boehmite particles and a binder to construct a continuous porous network. By mass percentage, the boehmite porous coating comprises: 92.0%–97.0% boehmite particles, 2.0%–5.0% acrylic binder, and 0.5%–2.0% dispersant. The porous base membrane can be made of polyethylene, polypropylene, or a composite of both. Without altering the definition of the boehmite surface facing the positive electrode and the interfacial parameters, the boehmite coating can be applied to one or both sides of the separator.
[0035] In some embodiments, the thickness of the boehmite porous coating is 1.0 μm to 4.0 μm, such as 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 4.0 μm, etc., or any value between adjacent values above. The volume median particle size D50 of the boehmite particles is 0.10 μm to 3.00 μm, such as 0.10 μm, 0.50 μm, 1.00 μm, 1.50 μm, 2.00 μm, 3.00 μm, etc., or any value between adjacent values above.
[0036] Furthermore, the winding tension of the separator is 0.28N to 0.65N, such as 0.28N, 0.35N, 0.40N, 0.50N, 0.55N, 0.65N, etc., or any value between these adjacent values. The winding tension of the separator is recorded online by the winding equipment, including contact coverage, gaps, and embedding. This invention utilizes the separator winding tension and the radial crushing intensity of large-diameter polycrystalline secondary particles to correspond to the interface geometry and particle mechanical response, respectively, enabling independent control and establishment of the correspondence between process parameters, interface states, and battery performance.
[0037] Electrolyte The electrolyte contains lithium hexafluorophosphate, carbonate solvent, and film-forming additives.
[0038] The specific type of carbonate solvent is not limited, such as ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc. The specific type of film-forming additive is not limited, such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), etc.
[0039] In some embodiments, the concentration of lithium hexafluorophosphate in the electrolyte is 0.8 mol / L to 1.2 mol / L; the carbonate solvent includes ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate, with a volume ratio of 20–30:40–50:25–35; the film-forming additives include vinylene carbonate, fluoroethylene carbonate, and lithium difluorophosphate, with mass fractions of 1.0%–3.0%, 0.5%–2.0%, and 0.2%–1.0% relative to the base electrolyte, respectively.
[0040] Interface adjustments See Figure 1 On the cross section maintaining the assembly relationship between the boehmite porous coating and the positive electrode active material layer, the section with a local spacing of no more than 0.20 μm and a continuous length of no less than 0.50 μm along the interface direction is identified as the actual contact section. The ratio of the sum of the projected lengths L1 of all actual contact sections to the total projected length L2 of the statistical interface is taken as the actual contact length ratio C1, where C1 = L1 / L2 × 100%, and the range of C1 is 20% to 70%, such as 20%, 30%, 40%, 50%, 60%, 70%, etc., or any value between the above adjacent values. Preferably, the range of C1 is 30% to 60%.
[0041] Figure 1 In the positive electrode current collector 1, there are many positive electrode material particles 2 in the positive electrode active material layer, and there are many boehmite particles 3 in the boehmite porous coating on the surface of the separator substrate 5. The non-contact area 4 refers to the area where the boehmite porous coating and the positive electrode active material layer do not reach the actual contact condition.
[0042] Furthermore, the local spacing in the non-real contact section is measured point by point, and the 90th percentile is used as the spacing parameter D1. The range of D1 is 0.30 to 2.00 μm, such as 0.30 μm, 0.50 μm, 0.80 μm, 1.00 μm, 1.50 μm, 2.00 μm, etc., or any value between the above adjacent values. Using the fitted baseline of the positive electrode active material layer surface without obvious depressions as a reference, the 90th percentile of the maximum normal depth of boehmite particles entering below the fitted baseline is used as the embedding parameter D2. The range of D2 is 0.20 μm to 1.50 μm, such as 0.20 μm, 0.40 μm, 0.60 μm, 0.80 μm, 1.00 μm, 1.50 μm, etc., or any value between the above adjacent values. The "90th percentile" refers to the value that corresponds to the cumulative distribution of the measured values of the same statistical object when they are sorted from smallest to largest.
[0043] Specifically, along the cross-section maintaining the positive electrode-separator assembly relationship, the shortest distance g(x) between the outer contour of the boehmite porous coating and the outer contour of the positive electrode active material layer is measured every 0.10 μm along the interface. When g(x) ≤ 0.20 μm and the length of the continuous segment formed by adjacent satisfying points is not less than 0.50 μm, it is considered a true contact segment. The sum of the projected lengths of all true contact segments is denoted as L1, and the total projected length of the interface is denoted as L2, C1 = L1 / L2 × 100%. For the dataset with g(x) > 0.20 μm, the 90th percentile is taken to obtain D1; the 90th percentile is taken to obtain D2 for the maximum normal depth of the boehmite particles entering the robustly fitted baseline of the positive electrode surface. C1, D1, and D2 are statistically analyzed from the cross-sectional images maintaining the assembly relationship, and their values affect the initial Rct, 40A polarization, and temperature. This invention distinguishes between insufficient contact, moderate contact, and excessive embedding using three quantifiable parameters: C1, D1, and D2, thus avoiding inferring the assembly interface state solely based on the thickness or permeability of the diaphragm ceramic layer. Taking the surface of the boehmite porous coating above the positive electrode active material layer as z=0, the region 0≤z≤10μm is defined as the near-surface layer Z1, and the region 15μm≤z≤25μm is defined as the bulk region Z2. F1, F2, F3, and F4 represent the proportions of damaged large-diameter polycrystalline secondary particles in Z1, Z2, Z1, and Z2, respectively, and are further defined as ΔF=∣(F1 F2) (F3 F4) | Calculate the difference in damage classification, where ΔF is the absolute value of the difference between the percentages, and the range of ΔF is 2% to 15%. For example, it can be 2, 3, 5, 8, 10, 12, 15 percentage points, or any value between adjacent values. Preferably, ΔF is 3% to 10%. This invention uses Z1 and Z2 partitions and separately calculates the damage ratio for large-diameter polycrystalline secondary particles and small-diameter single-crystal particles. ΔF is used to reduce the interference of rolling foundation damage and sample preparation errors on the judgment of interface stress.
[0044] Specifically, C1, D1, D2, and ΔF can be obtained through equal-resolution cross-sectional microscopic images and equivalent statistical algorithms, but the sampling position, pixel size, threshold, and number of particles must be kept consistent.
[0045] In some embodiments, the proportion F1 of damaged large-diameter polycrystalline secondary particles in Z1 ranges from 8% to 25%, such as 8%, 10%, 15%, 18%, 20%, 25%, etc., or any value between adjacent values. The proportion F2 of damaged large-diameter polycrystalline secondary particles in Z2 ranges from 3% to 12%, such as 3%, 5%, 7%, 9%, 10%, 12%, etc., or any value between adjacent values. The proportion F3 of damaged small-diameter single-crystal particles in Z1 ranges from 1% to 8%, such as 1%, 2%, 4%, 5%, 7%, 8%, etc., or any value between adjacent values. The proportion F4 of damaged small-diameter single-crystal particles in Z2 ranges from 0.5% to 5%, such as 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, etc., or any value between adjacent values. The values of F1, F2, F3, F4, and ΔF affect G1, G2, and the cycle retention rate.
[0046] Specifically, taking the surface of the boehmite porous coating on the positive electrode active material layer as z=0, and the direction towards the positive electrode current collector as the positive z direction, 0≤z≤10μm is defined as Z1, and 15μm≤z≤25μm is defined as Z2. Particles are classified according to the location of their closed contour centroid. A particle is considered damaged if it meets any of the following conditions: internal crack width is not less than 0.10μm and length is not less than 0.80μm; the area of the non-solid region accounts for not less than 5% of the closed contour area; or the particle body is split into at least three fragments with a spacing of not less than 0.10μm. The particle closed contour is the closed projected contour formed along the outer boundary of the particle in the BSE image, enclosing the continuous solid region of the particle; the area of the closed contour is the area enclosed by the closed projected contour.
[0047] [Battery and Performance] Press G1=(R1) The high-temperature positive electrode charge transfer resistance growth rate G1 is calculated as (R2) / R2×100%, where G1 is not greater than 35%, and can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, etc., or any value between the above adjacent values. R1 represents the positive electrode charge transfer resistance after storage at 60℃, and R2 represents the positive electrode charge transfer resistance in the initial state.
[0048] In some embodiments, R2 is 15 Ω·cm 2 ~60Ω·cm 2 For example, it can be 15Ω·cm 2 20Ω·cm 2 30Ω·cm 2 40Ω·cm 2 50Ω·cm 2 60Ω·cm2 "etc." can also be any value between the above adjacent values. According to G2=(R3) The positive charge transfer resistance growth rate G2 over 300 cycles is calculated as R2) / R2×100%. G2 is not greater than 45%, and can be 5%, 10%, 15%, 20%, 30%, 40%, 45%, etc., or any value between the above adjacent values.
[0049] In some embodiments, at 25±2℃, the voltage difference ΔV of the 40A platform 40 The maximum surface temperature of the battery cell is not greater than 0.255V, during 40A discharge and within 300 seconds after discharge, not exceeding 75℃. The capacity recovery rate after 7 days of storage at 60℃ is not less than 90%, and the capacity retention rate after 600 cycles is not less than 76%. Under the conditions of C1 of 20% to 70%, ΔF of 2% to 15%, and G1 not greater than 35%, the cell can balance a low 40A platform voltage difference, controlled battery temperature, high-temperature capacity recovery, and cycle capacity retention.
[0050] Specifically, R2, G1, G2, ΔV 40 Maximum temperature, capacity recovery, and cycle retention can be used to verify the correlation between interface state, particle damage, and electrochemical performance. During testing, SOC, temperature, current, and cutoff voltage are kept constant.
[0051] It should be noted that by adjusting the diaphragm winding tension to form appropriate real contact, gap and embedding state, and by adjusting the radial crushing strength of large-diameter polycrystalline secondary particles to control the classification damage difference between the near-surface layer and the bulk phase at the interface, the positive electrode charge transfer impedance and its growth rate are reduced, and high-temperature storage, rate discharge and cycle performance are improved.
[0052] In some embodiments, the lithium-ion battery has a diameter of 20mm to 22mm, such as 20.0mm, 20.5mm, 21.0mm, 21.5mm, 22.0mm, etc., or any value between these adjacent values. The height is 69mm to 72mm, such as 69mm, 70mm, 71mm, 72mm, etc., or any value between these adjacent values. The rated capacity of the cylindrical lithium-ion battery is 4.8Ah to 5.2Ah, such as 4.8Ah, 4.9Ah, 5.0Ah, 5.1Ah, 5.2Ah, etc., or any value between these adjacent values. At least one longitudinal edge of the positive and negative electrode sheets is provided with tab units spaced apart along the winding direction, forming an end current collecting structure after winding.
[0053] The cells of lithium-ion batteries can adopt single-end or double-end current collection structures, as long as the positive electrode-separator pairing interface, the classification of damage, and the positive electrode impedance growth under fixed test conditions meet the aforementioned range.
[0054] In summary, the lithium-ion battery provided by this invention uses a boehmite porous coating facing a high-nickel cathode, and determines the actual contact length ratio C1 based on the assembled cross-section; defines unfavorable gaps and unfavorable embeddings using D1 and D2 respectively, distinguishing between two types of deviations: insufficient contact and excessive indentation; fixes regions Z1 and Z2, statistically analyzes the damage to large-diameter polycrystalline secondary particles and small-diameter single-crystal particles respectively, and characterizes the classified response using ΔF; forms a controlled interface with a separator winding tension of 0.28–0.65 N, and forms a controlled particle response with a large particle radial crushing strength of 95–145 MPa. G1, G2, and ΔV are used as the parameters. 40 Maximum temperature, high temperature capacity recovery and cycle capacity maintenance verification interface, damage and kinetic relationship.
[0055] This invention provides a method for preparing a lithium-ion battery, comprising: preparing a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, followed by winding, heat setting, casing, current collector connection, electrolyte injection, sealing, formation, and capacity testing; wherein, by adjusting C1, D1, and D2 by adjusting the separator winding tension, and by adjusting ΔF by adjusting the radial crushing intensity of large-diameter polycrystalline secondary particles, the high-temperature storage, rate discharge, and cycle performance can be improved.
[0056] Lithium-ion batteries can take the form of battery modules, battery packs, etc.
[0057] This invention also provides an electrical device, including a lithium-ion battery provided in this invention, which is used to supply power.
[0058] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0059] Example 1 This embodiment provides a lithium-ion battery, the preparation steps of which are as follows: (1) Preparation of positive electrode slurry Layered lithium nickel cobalt manganese oxide (LiNi) with a nickel molar content of 91% was selected. 0.91 Co 0.05 Mn 0.04 O2 is used as the positive electrode active material. The large-particle polycrystalline secondary particles have a D50 of 12.8 μm and a radial crushing strength of 120 MPa, while the small-particle single-crystal particles have a D50 of 3.0 μm. The mass ratio of the two is 70:30.
[0060] By mass fraction, the solid components of the positive electrode slurry consist of 97.2% positive electrode active material, 0.8% conductive carbon black, 0.3% single-walled carbon nanotubes, and 1.7% polyvinylidene fluoride. Polyvinylidene fluoride was dissolved in N-methylpyrrolidone, and the conductive agent and positive electrode active material were added sequentially. After vacuum dispersion, the solid content of the slurry was adjusted to 65%.
[0061] (2) Preparation of positive electrode sheet A 12μm thick aluminum foil was selected, and the positive electrode slurry was coated on both sides of the foil surface. After drying at 120℃, the positive electrode sheet was obtained through rolling and slitting. The total areal density of the double-sided coating of the positive electrode active material layer was 24.5 mg / cm³. 2 The surface density of a single surface is 12.25 mg / cm³. 2 The thickness on one side is 34.5 μm, and the compaction density is 3.55 g / cm³. 3 During the rolling process, the linear pressure, roll gap, and belt speed are kept constant to ensure that the thickness difference of the active material layer on both sides of the positive electrode is no greater than 2μm.
[0062] The positive electrode cladding uses a 14mm diameter positive electrode disc, a lithium metal counter electrode, a 16μm thick polyethylene separator with a porosity of 40%±2%, and an electrolyte containing 2% VC at a volume ratio of 1.0mol / L LiPF6 / EC:EMC=3:7. The electrolyte injection volume is 80μL. After standing at 25±1℃ for 12h, it is charged and discharged for three cycles at 0.1C in the range of 3.00~4.30V. The discharge capacity in the third cycle is divided by the mass of the positive electrode active material to obtain the specific capacity of the positive electrode active material Qp=205mAh / g.
[0063] (3) Preparation of negative electrode slurry and electrode sheet The negative electrode slurry, by mass fraction, consists of 92.5% artificial graphite, 5.5% silicon-oxygen-graphite composite material, 0.5% conductive carbon black, 0.6% sodium carboxymethyl cellulose, and 0.9% styrene-butadiene rubber. The silicon oxide in the silicon-oxygen-graphite composite material has the chemical formula SiOx, where 0.8 ≤ x ≤ 1.3. Using deionized water as a solvent, the slurry solid content is 50%. The negative electrode slurry is coated on both sides of an 8μm thick copper foil, dried, rolled, and slit to obtain the negative electrode sheet. The total areal density of the double-sided coating of the negative electrode active material layer is 13.0 mg / cm³. 2 The surface density of a single surface is 6.50 mg / cm³. 2 The thickness on one side is 39.4 μm, and the compaction density is 1.65 g / cm³. 3 .
[0064] The negative electrode coin cell uses a 14mm diameter negative electrode disc, a lithium metal counter electrode, and the same separator and electrolyte as the positive electrode coin cell. The electrolyte injection volume is 80μL. After standing at 25±1℃ for 12 hours, it undergoes three cycles of lithium insertion and delithiation at 0.1C within the range of 0.005~1.50V. The delithiation capacity in the third cycle is divided by the mass of the negative electrode active material to obtain the specific capacity Q of the negative electrode active material. n=414mAh / g. The capacity ratio of the negative electrode to the positive electrode is calculated as N / P=[6.50×0.98×414] / [12.25×0.972×205]=1.08, where 0.98 is the mass fraction of the negative electrode active material and 0.972 is the mass fraction of the positive electrode active material; 6.50 is the areal density of the negative electrode active material layer and 12.25 is the areal density of the positive electrode active material layer.
[0065] (4) Preparation of diaphragm A 7 μm thick porous polyethylene membrane (42% porosity, average pore size 0.08 μm) was coated with boehmite slurry on one side. The solid component of the boehmite slurry consisted of 95.5% by mass boehmite, 3.5% by mass acrylic binder, and 1.0% by mass dispersant (ammonium polyacrylate); the boehmite D50 was 0.55 μm. After drying, a 2.5 μm thick porous boehmite coating was formed, resulting in a total membrane thickness of 9.5 μm.
[0066] (5) Electrolyte preparation The base electrolyte is 1.0 mol / L LiPF6, and the non-aqueous organic solvent is composed of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a volume ratio of 25:45:30. With the base electrolyte mass as 100%, 2.0% vinylene carbonate, 1.0% fluoroethylene carbonate and 0.5% lithium difluorophosphate are added.
[0067] (6) Winding and shaping The boehmite porous coating is placed facing the positive electrode active material layer and wound in the following order: negative electrode, separator, positive electrode, and separator. Spacer tabs are provided along the longitudinal edges of the positive and negative electrodes, forming an end current collector structure after winding. The separator winding tension is set to 0.45 N; after winding, it is heat-set at 80°C and 0.20 MPa radial pressure for 180 s. The heat-setting temperature, radial pressure, and time remain constant in the remaining examples.
[0068] (7) Assembly, liquid injection and sealing The core is inserted into a steel shell with a diameter of approximately 21 mm and a height of approximately 70 mm, and the current collector connection and sealing of the positive and negative terminals are completed. Electrolyte is added at a filling coefficient of 2.6 g per ampere-hour of the rated capacity of the cell, and the mixture is allowed to stand at 25°C for 24 hours to allow the electrolyte to fully impregnate the cells.
[0069] (8) Transformation and separation The battery cell was charged to 3.60V at 0.05C at 25℃, then charged to 4.20V at 0.1C and kept constant at 0.05C for 12 hours; then discharged to 2.80V at 0.2C. This process was repeated for two weeks, followed by aging at 45℃ for 48 hours, and then capacity testing at 25℃.
[0070] The obtained cell has a 0.2C capacity of 5.02 Ah. The interface parameters are C1 = 47%, D1 = 1.10 μm, D2 = 0.65 μm; F1 = 15.0%; F2 = 7.0%; F3 = 4.0%; F4 = 2.0%, and the classification damage difference ΔF is 6.0 percentage points.
[0071] In Example 1, R² was 32.00 Ω·cm. 2 R1 is 37.76 Ω·cm 2 R3 is 39.68 Ω·cm 2 According to the fixed formula, G1 is calculated to be 18% and G2 is calculated to be 24%.
[0072] After testing, ΔV 40 =0.218V, maximum temperature 65.0℃, capacity recovery rate 96.2%, 600-cycle retention rate 89.0%.
[0073] Example 2 The difference between this embodiment and Embodiment 1 is that the diaphragm winding tension is adjusted to 0.28N, so that the diaphragm winding tension changes from 0.45N to 0.28N; otherwise, it is the same as Embodiment 1.
[0074] Example 3 The difference between this embodiment and Embodiment 1 is that the diaphragm winding tension is adjusted to 0.65N, thus changing the diaphragm winding tension from 0.45N to 0.65N; otherwise, it is the same as Embodiment 1.
[0075] Example 4 The difference between this embodiment and Embodiment 1 is that the diaphragm winding tension is adjusted to 0.35N, thus changing the diaphragm winding tension from 0.45N to 0.35N; otherwise, it is the same as Embodiment 1.
[0076] Example 5 The difference between this embodiment and Embodiment 1 is that the diaphragm winding tension is adjusted to 0.55N, thus changing the diaphragm winding tension from 0.45N to 0.55N; otherwise, it is the same as Embodiment 1.
[0077] Example 6 The difference between this embodiment and Embodiment 1 is that the radial crushing strength of the large-diameter polycrystalline secondary particles is adjusted to 95 MPa, thereby changing the radial crushing strength of the large-diameter polycrystalline secondary particles from 120 MPa to 95 MPa; otherwise, it is the same as Embodiment 1.
[0078] Example 7 The difference between this embodiment and Embodiment 1 is that the radial crushing strength of the large-diameter polycrystalline secondary particles is adjusted to 145 MPa, thereby changing the radial crushing strength of the large-diameter polycrystalline secondary particles from 120 MPa to 145 MPa; otherwise, it is the same as Embodiment 1.
[0079] Example 8 The difference between this embodiment and Embodiment 1 is that the radial crushing strength of the large-diameter polycrystalline secondary particles is adjusted to 105 MPa, thereby changing the radial crushing strength of the large-diameter polycrystalline secondary particles from 120 MPa to 105 MPa; otherwise, it is the same as Embodiment 1.
[0080] Example 9 The difference between this embodiment and Embodiment 1 is that the radial crushing strength of the large-diameter polycrystalline secondary particles is adjusted to 135 MPa, thereby changing the radial crushing strength of the large-diameter polycrystalline secondary particles from 120 MPa to 135 MPa; otherwise, it is the same as Embodiment 1.
[0081] Example 10 The difference between this embodiment and Embodiment 1 is that the mass ratio of large-diameter polycrystalline secondary particles to small-diameter single-crystal particles is adjusted to 80:20; otherwise, it is the same as Embodiment 1.
[0082] Comparative Example 1 The difference between this comparative example and Example 1 is that the diaphragm winding tension is adjusted to 0.15N, thus changing the diaphragm winding tension from 0.45N to 0.15N; otherwise, it is the same as Example 1.
[0083] Comparative Example 2 The difference between this comparative example and Example 1 is that the diaphragm winding tension is adjusted to 0.85N, thus changing the diaphragm winding tension from 0.45N to 0.85N; otherwise, it is the same as Example 1.
[0084] Comparative Example 3 The difference between this comparative example and Example 1 is that the radial crushing strength of the large-diameter polycrystalline secondary particles is adjusted to 75 MPa, thus changing the radial crushing strength of the large-diameter polycrystalline secondary particles from 120 MPa to 75 MPa; otherwise, it is the same as Example 1.
[0085] Comparative Example 4 The difference between this comparative example and Example 1 is that the radial crushing strength of the large-diameter polycrystalline secondary particles is adjusted to 165 MPa, thus changing the radial crushing strength of the large-diameter polycrystalline secondary particles from 120 MPa to 165 MPa; otherwise, it is the same as Example 1.
[0086] Comparative Example 5 The difference between this comparative example and Example 1 is that the inorganic particle type of the diaphragm ceramic layer is adjusted to α-Al2O3, so that the inorganic particles of the diaphragm ceramic layer are changed from boehmite to an equal mass of α-Al2O3; otherwise, it is the same as Example 1.
[0087] All continuous variable series are based on Example 1. In the examples or comparative examples where only the diaphragm winding tension is changed, the heat setting temperature, radial pressure, setting time, particle crushing strength, coating material, and coating thickness remain unchanged; in the examples or comparative examples where only the radial crushing strength is changed, the diaphragm winding tension, roller pressure, heat setting conditions, particle size, and cathode formulation remain unchanged; in the material category comparative examples, boehmite is replaced with an equal mass of Al2O3, and the ceramic particle D50, coating solid content, binder ratio, coating thickness, and winding conditions are consistent with Example 1. Except for the factors listed, all other conditions are kept consistent in each group.
[0088] Batch control instructions for strength group materials: Examples 6 to 9, as well as Comparative Examples 3 and 4, selected different batches of cathode materials with the same Ni molar content, D50, single crystal / polycrystalline mass ratio, and surface treatment indicators, except for radial crushing strength. Radial crushing strength grades of 95 MPa, 145 MPa, 105 MPa, 135 MPa, 75 MPa, and 165 MPa were determined and screened according to the fixed micro-compression method specified in this invention. The cathode slurry ratio, solid content, coating density, roller pressing line pressure, diaphragm winding tension, heat setting conditions, and assembly formation process for each batch were the same as in Example 1. The only difference between the groups was the radial crushing strength.
[0089] Test methods and calculation formulas 1. Interfacial Section Preparation. The battery cell was discharged at 0.2C to 2.80V, allowed to stand for 2 hours, and then disassembled in an argon atmosphere with a dew point not exceeding -40℃ and O2 and H2O contents not exceeding 1ppm. Maintaining the stacked state of the positive electrode, separator, and negative electrode, a 5mm × 5mm sample was cut and pre-fixed at -80±5℃ for 30 minutes. Vacuum impregnation was performed using epoxy resin with a curing volume shrinkage rate not exceeding 0.5%, followed by curing at a clamping pressure of 0.15±0.02MPa and 25±2℃ for 24 hours. The cross-section was then obtained by argon ion beam polishing.
[0090] 2. C1, D1, and D2. BSE images were acquired using field emission scanning electron microscopy at an accelerating voltage of 5 kV and a working distance of 8 mm, with a fixed pixel size of 0.05 μm. EDS was used to confirm the co-location region of Al and O. Three cross-sections were taken at 10% ± 2%, 50% ± 2%, and 90% ± 2% of the effective length of the positive electrode for each cell, with a statistical interface length of not less than 200 μm for each cross-section. The actual contact length ratio was calculated as C1 = L1 / L2 × 100%; for datasets with g(x) > 0.20 μm, P was taken. 90 D1 is obtained; the embedding depths of each measuring point are sequentially denoted as E1, E2, ..., E m and for E1 to E m Take P 90 D2 is obtained.
[0091] 3. Damage Classification. Two particle types were distinguished using BSE images and EBSD orientation maps from the same field of view. At least 100 particles were counted for each particle type in Z1 and Z2. F1, F2, F3, and F4 were calculated by dividing the number of damaged large-diameter particles in Z1, the number of damaged large-diameter particles in Z2, the number of damaged small-diameter particles in Z1, and the number of damaged small-diameter particles in Z2 by the total number of particles in the corresponding region and type, and then multiplying by 100%; ΔF = |(F1 F2) (F3 F4)∣.
[0092] 4. Positive electrode symmetrical battery EIS. Initially, the cells were charged at 25±1℃ at 0.5C to 4.20V and held constant at 0.05C, then discharged at 0.5C to 50%±2% SOC, and left to stand for 2 hours before disassembly. High-temperature cells, after being stored at 60±1℃ for 7 days, were returned to a 25±1℃ environment and left to stand for 6 hours, then discharged at 0.5C to adjust to 50%±2% SOC, and left to stand for 2 hours before disassembly. After completing the 300th cycle, the 300-cycle cells were charged at 25±1℃ using the same charging regime to 4.20V and held constant at 0.05C, then discharged at 0.5C to adjust to 50%±2% SOC, and left to stand for 2 hours before disassembly. For each group, 12mm diameter positive electrode discs were punched from the middle position of the core at 50%±2% of the effective coating length, using the same radial layers. These discs were rinsed three times with dimethyl carbonate for 30 seconds each time and then vacuum-dried at 25℃ for 2 hours. Two positive electrode discs from the same group were placed opposite each other, using a 16μm thick polyethylene diaphragm with a porosity of 40%±2%, an electrolyte with a 1.0mol / L LiPF6 / EC:EMC volume ratio of 3:7 and containing 2% VC by mass, an injection volume of 80μL, and an assembly pressure of 0.20±0.02MPa. The discs were then allowed to stand at 25±1℃ for 12 hours. Tests were conducted at 25±1℃ using a 5mV sinusoidal perturbation, a frequency range of 100kHz to 10mHz, with 10 points per decade, and a fixed equivalent circuit of Rs-(Rf∥CPEf)-(Rct∥CPEdl)-W for fitting. Let the total charge transfer resistance of the fitted symmetrical battery be R. ct,sym If the area of a single circular piece is A, then R ct,p =R ct,sym ×A / 2;G1=(R1 R2) / R2×100%;G2=(R3 ... R2) / R2×100%. Among them, Rct,p obtained from the initial group is denoted as R2, Rct,p obtained from the high temperature group is denoted as R1, and Rct,p obtained from the 300-week group is denoted as R3.
[0093] 5. High-temperature storage. The cells were charged at a constant current of 0.5C to 4.20V at 25±1℃ and then at a constant voltage of 0.05C. After standing for 2 hours, they were stored at 60±1℃ for 7 days. After storage, they were returned to 25±1℃ and stood for 6 hours. Cells used for capacity recovery testing were discharged at 0.2C to 2.80V. The capacity recovery rate = (0.2C discharge capacity after storage / 0.2C discharge capacity before storage) × 100%. Cells used for positive electrode EIS were adjusted to 50%±2% SOC according to the method in section 4, stood for 2 hours, and symmetrical cells were constructed by taking circular wafers of the same area from the same layer in the core.
[0094] 6. 40A Platform Voltage Difference and Maximum Temperature. The cell was discharged at 0.2C at 25±2℃ to obtain a reference curve, and then discharged at 40A to 2.80V after recovering to the same initial state of charge. V 0.2C and V 40A Take the average voltage ΔV in the range of 20% to 80% state of charge. 40 =V 0.2C -V 40A The thermocouple was fixed at the midpoint of the housing along the axis, and the temperature was continuously recorded from the start of the 40A discharge to 300s after the discharge ended, with the highest value being recorded.
[0095] 7. Cycling Performance. The cells were charged at 25±2℃ with a constant current of 8A to 4.20V, then constant voltage until the current did not exceed 0.5A, and allowed to stand for 10 minutes; subsequently discharged at a constant current of 40A to 2.80V, and allowed to stand for 10 minutes, constituting one cycle. The capacity was calibrated at 0.2C every 100 cycles. Capacity retention at 600 cycles = (calibrated capacity at 600 cycles / initial calibrated capacity) × 100%. At the 300-cycle node, the cells were uniformly adjusted to 50%±2% SOC according to the method in section 4, allowed to stand for 2 hours, and positive electrode discs of the same area were taken from the same layer in the middle of the core. R3 was obtained under identical conditions of separator, electrolyte, injection volume, assembly pressure, temperature, frequency, and equivalent circuit. Twelve cells were prepared for each embodiment and comparative example: three for initial interface and EIS, three for high-temperature storage, three for the 300-cycle node, and three for 600-cycle cycling and overall battery testing.
[0096] The raw EIS data and growth rate of the positive electrode of the product obtained from the examples and comparative examples are shown in Tables 1 and 2, and the test results of high temperature storage, rate discharge and cycle performance are shown in Table 3.
[0097] Table 1. Raw EIS data and growth rate of the positive electrode of the products obtained from the examples and comparative examples.
[0098] Table 2. Evaluation factors and performance test results of the products obtained from the examples and comparative examples.
[0099] Table 3 shows the high-temperature storage, rate discharge, and cycle performance of the products obtained from the examples and comparative examples.
[0100] Analysis of experimental results: (1) Effect of diaphragm winding tension Comparing Examples 1 to 5 and Comparative Examples 1 and 2, it can be seen that when the cathode formulation, radial crushing strength of large-diameter polycrystalline secondary particles, separator coating composition, heat setting temperature, 0.20 MPa heat setting radial pressure, and 180 s setting time remain unchanged, this group only changes the separator winding tension. When the tension is reduced from 0.45 N in Example 1 to the lower limit of 0.28 N in Example 2, C1 decreases from 47% to 31%, D1 increases from 1.10 μm to 1.85 μm, D2 decreases from 0.65 μm to 0.30 μm, and R2 increases from 32 Ω·cm. 2 Increased to 40Ω·cm 2 , ΔV 40 Increasing the voltage from 0.218V to 0.239V, the capacity retention after 600 cycles decreased from 89.0% to 82.0%. When the tension was further reduced to 0.15N (comparative example 1), C1 decreased to 12%, D1 increased to 3.30μm, and G1 and G2 increased to 54% and 66% respectively, but the capacity retention was only 69.0%. This is because the excessively low tension prevents the separator from stably adhering to the positive electrode surface, widening the non-contact gap and allowing Li in the electrolyte to escape. + The electrolyte needs to travel a longer and more dispersed liquid phase path to reach the positive electrode. Uneven local ion flux leads to concentrated surface reactions under high charge conditions and accelerates the formation of a high-resistivity interfacial film. On the other hand, when the tension is increased to the upper limit of 0.65N in Example 3, C1 increases to 65% and D2 increases to 1.40μm, while G1 remains at 33% and G2 at 44%. However, when the tension is further increased to 0.85N in Comparative Example 2, C1 reaches 82%, D2 reaches 2.35μm, ΔF reaches 16.5 percentage points, and G1 and G2 deteriorate to 56% and 70%, respectively. This is because excessive tension causes the boehmite coating to protrude and continuously press into the near-surface layer of the positive electrode. The contact load is concentrated at the primary particle boundary of the polycrystalline secondary particles, and cracks and material defects expose fresh surfaces, promoting electrolyte side reactions, electron contact attenuation, and interfacial impedance growth. Therefore, the tension range of 0.28 to 0.65 N simultaneously addresses both insufficient contact and excessive embedding at the two side boundaries, allowing C1, D1, and D2 to remain within a range that balances ion transport and mechanical integrity.
[0101] (2) Influence of radial crushing strength of large-diameter polycrystalline secondary particles Comparing Examples 1, 6 to 9, and Comparative Examples 3 and 4, it can be seen that the diaphragm winding tension was fixed at 0.45 N, the heat-setting radial pressure was fixed at 0.20 MPa, and the surface density, compaction density, particle size, and ratio of the two types of particles of the positive electrode active material were all kept consistent. Only the radial crushing strength of the large-diameter polycrystalline secondary particles was changed in this group. Therefore, in all examples, C1 was 47%, D1 was 1.10 μm, and D2 was 0.65 μm; the interface geometry did not contribute to the performance differences. When the radial crushing strength was reduced from 120 MPa in Example 1 to the lower limit of 95 MPa in Example 6, F1 increased from 15.0% to 22.0%, ΔF increased from 6.0 percentage points to 11.5 percentage points, G1 increased from 18% to 32%, G2 increased from 24% to 43%, and the 600-cycle capacity retention decreased from 89.0% to 79.0%. Further reduction to 75 MPa (Comparative Example 3) resulted in F1 reaching 29.0%, ΔF reaching 16.5 percentage points, G2 increasing to 64%, and the capacity retention decreasing to 67.0%. Lower crushing strength indicates insufficient primary particle bonding strength, making it easier for polycrystalline secondary particles to crack along grain boundaries under the same interfacial load. After crack propagation, electrolyte enters the particle interior, forming a new positive electrolyte interface and disrupting the intraparticle electron pathways, ultimately amplifying both high-temperature impedance growth and cycle decay. When the strength was increased to the upper limit of 145 MPa in Example 7, ΔF decreased to 2.7 percentage points, while still achieving 34 Ω·cm. 2 The R² and 600-cycle capacity retention were achieved; when the strength was further increased to 165 MPa (comparative example 4), ΔF decreased by 1.6 percentage points, but R² actually increased to 44 Ω·cm. 2 With G1 increasing to 39%, the capacity retention rate decreased to 75.0%. Excessive strength particles, under fixed rolling conditions, resulted in insufficient deformation and rearrangement, reducing the actual electron contact area between particles and widening the local porosity distribution in the active layer. Although near-surface breakage at the interface decreased, it created significant solid-phase contact resistance and weakened the consistency of electrolyte channels. Therefore, 95–145 MPa can maintain compacted contact of the electrode while suppressing excessive breakage of polycrystalline secondary particles.
[0102] (3) Influence of the type of inorganic particles in the diaphragm ceramic layer Comparing Example 1 and Comparative Example 5, it can be seen that the membrane base film, ceramic particle D50, ceramic layer thickness, binder type and ratio, membrane winding tension, heat setting conditions, positive and negative electrode formulations, and electrolyte are all consistent. This group only changed the type of inorganic particles in the ceramic layer, replacing boehmite with α-Al2O3. The C1 of both examples is 47% and 47%, respectively, and the D1 is 1.10 μm and 1.05 μm, respectively, indicating that the macroscopic contact coverage and non-contact gap are similar. However, in Comparative Example 5, D2 increased from 0.65 μm to 0.85 μm, F1 increased from 15.0% to 18.5%, ΔF increased from 6.0 percentage points to 8.5 percentage points, and R2 increased from 32 Ω·cm. 2 Increased to 38Ω·cm 2 The percentages of G1 and G2 increased from 18% to 42%, and the 600-cycle capacity retention decreased from 89.0% to 72.0%. Under the same geometric dimensions and assembly load, boehmite particles and their bonding interface exhibit better contact compliance with high-nickel cathode surfaces. They can disperse radial loads through local adjustments of particle micro-displacement and coating pores, while maintaining continuous electrolyte channels. The local contact points formed by α-Al2O3 particles have higher rigidity, and the load is more concentratedly transferred to the surface of polycrystalline secondary particles, resulting in more grain boundary opening and micro-area material loss near the interface surface, and accelerating side reactions on the newly formed surface at high temperatures and high potentials. Therefore, the boehmite material, along with C1, D2, and ΔF, works in conjunction, and its effect is determined by the contact compliance of the ceramic material, interfacial stress distribution, and cathode kinetics.
[0103] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A lithium-ion battery, characterized in that, The device includes a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The positive active material layer comprises large-diameter polycrystalline secondary particles and small-diameter single-crystal particles. Both the large-diameter polycrystalline secondary particles and the small-diameter single-crystal particles are layered lithium-containing transition metal oxide particles. In the layered lithium-containing transition metal oxide particles, the molar percentage of nickel in the total transition metal is greater than or equal to 88%. The separator includes a porous base membrane and a boehmite porous coating disposed on at least one surface of the porous base membrane, wherein the boehmite porous coating faces the positive electrode active material layer. On the cross section maintaining the assembly relationship between the boehm porous coating and the positive electrode active material layer, the section with a local spacing of no more than 0.20 μm and a continuous length of no less than 0.50 μm along the interface direction is identified as the actual contact section. The ratio of the sum of the projected lengths L1 of all actual contact sections to the total projected length L2 of the statistical interface is taken as the actual contact length ratio C1, where C1 = L1 / L2 × 100%, and the range of C1 is 20% to 70%. Taking the surface of the positive electrode active material layer relative to the boehmite porous coating as z=0, the region 0≤z≤10μm is defined as the near-surface layer Z1, and the region 15μm≤z≤25μm is defined as the bulk region Z2. F1, F2, F3, and F4 represent the proportions of damaged large-diameter polycrystalline secondary particles in Z1, Z2, Z1, and Z2, respectively, and are further defined as ΔF=|(F1... F2) (F3 F4) | Calculate the classification damage difference, where ΔF is the difference between the number proportions expressed as a percentage, ranging from 2% to 15%.
2. The lithium-ion battery according to claim 1, characterized in that, The equivalent circular diameter of the large-diameter polycrystalline secondary particles is 8μm to 20μm, and the equivalent circular diameter of the small-diameter single-crystal particles is 1μm to 6μm; preferably, the equivalent circular diameter of the large-diameter polycrystalline secondary particles is 10μm to 16μm, and the equivalent circular diameter of the small-diameter single-crystal particles is 1.5μm to 5.0μm; the mass ratio of the large-diameter polycrystalline secondary particles to the small-diameter single-crystal particles is 60:40 to 85:
15.
3. The lithium-ion battery according to claim 1, characterized in that, The range of C1 is 30% to 60%; Preferably, the local spacing is measured point by point in the non-real contact section, and the 90th percentile is used as the gap parameter D1, wherein the range of D1 is 0.30 to 2.00 μm; the baseline fitted to the surface of the positive electrode active material layer without obvious depression is used as a reference, and the 90th percentile of the maximum normal depth of the boehmite particles entering below the fitted baseline is used as the embedding parameter D2, wherein the range of D2 is 0.20 μm to 1.50 μm.
4. The lithium-ion battery according to claim 1, characterized in that, The range of F1 is 8% to 25%, the range of F2 is 3% to 12%, the range of F3 is 1% to 8%, the range of F4 is 0.5% to 5%, and the range of ΔF is 3% to 10%.
5. The lithium-ion battery according to claim 1, characterized in that, Press G1=(R1) The high-temperature positive electrode charge transfer resistance growth rate G1 is calculated as R2) / R2×100%, where G1 is not greater than 35%, R1 represents the positive electrode charge transfer resistance after storage at 60℃, and R2 represents the positive electrode charge transfer resistance in the initial state. Preferably, R2 is 15 Ω·cm 2 ~60Ω·cm 2 ; Preferably, according to G2=(R3) The positive charge transfer resistance growth rate G2 over 300 cycles is calculated as (R2) / R2×100%, and G2 is not greater than 45%.
6. The lithium-ion battery according to claim 1, characterized in that, The winding tension of the diaphragm is 0.28N to 0.65N; Preferably, the radial crushing strength of the large-diameter polycrystalline secondary particles is 95 MPa to 145 MPa; Preferably, the thickness of the boehmite porous coating is 1.0 μm to 4.0 μm, and the volume median particle size (D50) of the boehmite particles is 0.10 μm to 3.00 μm.
7. The lithium-ion battery according to claim 1, characterized in that, The thickness of the positive electrode active material layer on one side is 30μm to 42μm, and the thickness difference of the positive electrode active material layer on the two surfaces of the positive electrode current collector is no greater than 4μm. Preferably, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector, wherein the negative active material layer comprises artificial graphite and a silicon-oxygen-graphite composite material; preferably, the mass ratio of the artificial graphite to the silicon-oxygen-graphite composite material is 90:10 to 96:
4. Preferably, the electrolyte comprises lithium hexafluorophosphate, a carbonate solvent, and a film-forming additive; preferably, the concentration of lithium hexafluorophosphate in the electrolyte is 0.8 mol / L to 1.2 mol / L; the carbonate solvent comprises ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate, with a volume ratio of 20–30:40–50:25–35; the film-forming additive comprises vinylene carbonate, fluoroethylene carbonate, and lithium difluorophosphate, with mass fractions of 1.0%–3.0%, 0.5%–2.0%, and 0.2%–1.0%, respectively. Preferably, the lithium-ion battery is a cylindrical lithium-ion battery with a diameter of 20mm to 22mm, a height of 69mm to 72mm, and a rated capacity of 4.8Ah to 5.2Ah; at least one longitudinal edge of the positive electrode and the negative electrode are respectively provided with tab units formed at intervals along the winding direction, which form an end current collection structure after winding.
8. The lithium-ion battery according to any one of claims 1 to 7, characterized in that, At 25±2℃, the voltage difference ΔV of the 40A platform 40 The maximum surface temperature of the casing during a 40A discharge and within 300 seconds after the discharge is not higher than 75°C. The capacity recovery rate after 7 days of storage at 60°C is not less than 90%, and the capacity retention rate after 600 cycles is not less than 76%.
9. A method for preparing a lithium-ion battery according to any one of claims 1 to 8, characterized in that, include: Positive electrode sheet, negative electrode sheet, separator and electrolyte are prepared separately, and then wound, heat set, shelled, current collector connected, liquid injected, sealed, formed and capacity divided. C1 is adjusted by the diaphragm winding tension, and ΔF is adjusted by the radial crushing strength of the large-diameter polycrystalline secondary particles. Preferably, it further includes adjusting D1 and D2 by adjusting the diaphragm winding tension.
10. An electrical appliance, characterized in that, This includes the lithium-ion battery described in any one of claims 1 to 8 or the lithium-ion battery prepared by the preparation method described in claim 9.